Novel Eyelid Supraorbital Pretemporal Approach to the Anterior Communicating Artery Complex: A Quantitative Cadaveric Comparative Study - Zhao, Xiaochun; Evans, Alexander R.; Shi, Helen H.; Pelargos, Panayiotis E.; Tan, Jeremy; Do, Thai; Dunn, Ian F.; Graffeo, Christopher; Bauer, Andrew M. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Objectives Access to the anterior communicating artery (ACom) complex may be achieved via the modified orbito-zygomatic (mOZ) or eyelid supraorbital (ES) approaches. Further, the ES approach may improve cosmesis at the cost of decreased exposure and maneuverability. Thus, a novel eyelid supraorbital pretemporal (ESP) approach, a combination of the ES approach with a pretemporal dissection, may optimize the shortcomings of the ES approach.Design This is a cadaveric study.Setting Five ES, ESP, and mOZ approaches were performed on cadaveric heads and compared.Participants Cadaveric specimens were provided under the University of Oklahoma Health Science Center's Willed Body Program.Main Outcome Measures Quantitative measures of exposure, maneuverability, and angles of attack in horizontal and vertical planes were compared between approaches.Results The ESP approach was superior in terms of exposure and deep maneuverability when compared with the ES approach (p < 0.01). In addition, this approach demonstrated superior angles of attack in vertical (p < 0.01) and horizontal (p = 0.045) planes. When compared with the mOZ approach, the ESP approach provided significantly greater exposure to the contralateral A2 (p < 0.01) with a less favorable horizontal angle of attack (p < 0.01). The ESP provides exact exposure to complete the pretemporal osteotomy, offering a unique perspective on the ACom complex.Conclusion When accessing the ACom complex, the ESP approach yields superior exposure and maneuverability compared with the ES approach and is comparable to the mOZ approach, with unique advantages provided by the addition of pretemporal osteotomy and dissection.
Keywords: supraorbital approach; orbito-zygomatic approach; anterior communicating artery complex; cadaveric analysis